Changing Nature of Capitalism in the Era of Globalization through YouTube: A Perspective of Consumerism - Nath, Dipika (Jurnal Perpajakan dan Keuangan Publik, 2024)
The contemporary concept of globalization emerged during the 1980s under the influence of leaders like Ronald Reagan and Margaret Thatcher, who promoted privatization as a pathway to globalization. This idea gained widespread popularity in the 1990s. Postmodern scholars such as Paul-Michel Foucault, Jean Baudrillard, Arjun Appadurai, and Douglas Kellner argue that globalization is a top-down process legitimizing capitalist logic, where technology plays a pivotal role in fostering "techno-capitalism." In the 21st century, digital media platforms have become instrumental in generating surplus value for capitalism through various mechanisms. YouTube, as a prominent video-sharing platform launched in 2005, has played a significant role in this process. This research critically examines the role of YouTube in promoting consumerism as a tool of capitalism, exploring its impact on modern digital economies and cultural consumption patterns.